The railway children - - Nesbit, Edith; Freeman, Michael Lacey (Pakistan : Maqbool Books, 2015)
This Teen ELI Readers adaptation of The Railway Children by Edith Nesbit is tailored for A1-level English learners. The story follows three young siblings who move to a new home after their father is unexpectedly removed from their lives. Initially saddened and disoriented, they gradually adapt, make new friendships, and embark on heartwarming adventures. The language is simplified to suit beginner readers, and it's accompanied by an audio CD to support listening comprehension and pronunciation$1 (Bmaking it a great resource for learning English through classic children's literature.s
Keywords: English Literature - Text Book